Structural analysis according to the method of boundary elements of circular in terms of foundation construction - Morhun, A. S.; Franchuk, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Structural analysis of circular foundation of the building based on the calculated resiliently-plastic model which takes into account deviatoric and ball stress components and the nonlinear three-dimensional soil deformation when changing the degree of soil foundation compaction